Ambiente Virtual para Modelagem dos Canais Radiculares - Bogoni, Tales Nereu; Pinho, Márcio Sarroglia (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2014: Anais do XIV Workshop de Informática Médica, 2014)
This paper presents a simulator based on Virtual Reality equiped with a custom haptic device that allows the simulation of movements with endodontic files. Through an experiment tested by users with experience in endodontics has been proven that the method is effective at identifying errors on the sequence of instrumentation.